Cutting edge: direct suppression of B cells by CD4+ CD25+ regulatory T cells. - Lim, H; Hillsamer, P; Banham, A; Kim, C (2005)
Regulatory T cells (Tregs) can potentially migrate to the B cell areas of secondary lymphoid tissues and suppress T cell-dependent B cell Ig response. T cell-dependent Ig response requires B cell stimulation by Th cells. It has been unknown whether Tregs can directly suppress B cells or whether they must suppress Th cells to suppress B cell response. We report here that Foxp3+ Tregs are found in T-B area borders and within germinal centers of human lymphoid tissues and can directly suppress B cell Ig response. Although Tregs can effectively suppress T cells, they can also directly suppress B cell response without the need to first suppress Th cells. The direct suppression of B cell Ig production by Tregs is accompanied by inhibition of Ig class switch recombination.